PERANG, MILITER DAN MASYARAKAT: Pemerintahan Militer pada Masa Revolusi dan Pengaruhnya pada Indonesia Kini - Ari Sapto (Jurnal Sejarah dan Budaya, 2013)
Abstract. Based on continuity and discontinuity of past time of historical consciousness, there were many realities occurred during National Revolution (1945-1949) that remain exists today. The presence of Military Government in last quarter of revolution period happened in situation of independence defend war. War was seen frequently as early one source of militarism existence in Indonesia society today. The absence of Deutch does not decrease perception of threat existence yet. The continuity of threat perception becomes as icon in Indonesia history that is reproduced continually.